2012
DOI: 10.1103/physreve.85.015304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of reaction-driven miscible viscous fingering

Abstract: An experimental demonstration of reaction-driven viscous fingering developing when a more viscous solution of a reactant A displaces a less viscous miscible solution of another reactant B is presented. In the absence of reaction, such a displacement of one fluid by another less mobile one is classically stable. However, a simple A + B → C reaction can destabilize this interface if the product C is either more or less viscous than both reactant solutions. Using the pH dependence of the viscosity of some polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 33 publications
5
76
0
Order By: Relevance
“…We directly compare the spatio-temporal evolution of the concentration fields in the reactive cases to the analogous non reactive scenarios obtained by neglecting kinetic terms in Eqs. (13)- (15). A consistent comparison is made by using the same general conditions and parameters (R a = 2.5, δ a = 0.64) both in the non reactive and reactive cases, the latter ones also considering the parameters for the species C, R c = 2.3, and δ c = 0.48.…”
Section: Nonlinear Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We directly compare the spatio-temporal evolution of the concentration fields in the reactive cases to the analogous non reactive scenarios obtained by neglecting kinetic terms in Eqs. (13)- (15). A consistent comparison is made by using the same general conditions and parameters (R a = 2.5, δ a = 0.64) both in the non reactive and reactive cases, the latter ones also considering the parameters for the species C, R c = 2.3, and δ c = 0.48.…”
Section: Nonlinear Simulationsmentioning
confidence: 99%
“…13,14 This change in turn can affect the flows but in some cases can also more drastically modify the patterns or even trigger an instability in an otherwise stable system. 15 In the case of buoyancy-driven instabilities, such a chemo-hydrodynamic coupling has already been well studied for traveling autocatalytic fronts (see Refs. [16][17][18] and references therein) and combustion problems.…”
Section: Introductionmentioning
confidence: 99%
“…There is however increased interest in understanding the properties of such thin stripes either to suppress them or to avoid confusing them with other patterns due to other instabilities. Recent work has indeed demonstrated that chemical reactions that change the viscosity of polymer solutions [12][13][14] can generate patterns at the interface between miscible solutions even in the viscously stable case of a more viscous injected fluid displacing a less viscous one. In such reaction-induced viscous fingering, 14 the pattern-forming role played by reactions modifying the viscosity in situ can only be appreciated if the underlying non-reactive displacement is stable, which is not trivial when the above mentioned stripes come into play.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] For A þ B ! C fronts, complex buoyancy- 18,19 or viscosity-driven patterns [20][21][22] can develop when miscible solutions containing initially separated A and B reactants are put into contact with each other. These convective patterns have been shown to have stability properties 21,22 and symmetries 18 different from those in non-reactive systems.…”
Section: Introductionmentioning
confidence: 99%
“…C fronts, complex buoyancy- 18,19 or viscosity-driven patterns [20][21][22] can develop when miscible solutions containing initially separated A and B reactants are put into contact with each other. These convective patterns have been shown to have stability properties 21,22 and symmetries 18 different from those in non-reactive systems. Finally, a third class of model systems consists of immiscible RDC fluid-fluid systems in the presence of species which are either restricted to the fluid-fluid interface or can cross the interface, and which may also undergo chemical reactions.…”
Section: Introductionmentioning
confidence: 99%